Highly anisotropic distribution of iron nanoparticles within MCM-41 Mesoporous Silica - Moreno, Mario Sergio Jesus (2006)
Electron microscopy techniques are used to visualize the spatial distribution of iron nanoparticles inside a mesoporous MCM-41 molecular sieve. Direct observation of the iron oxide nanoparticles by STEM-HAADF imaging reveals a highly non-uniform spatial distribution inside the mesopores. These particles are retained in the pores after a reduction treatment unlike the behavior found in other similar systems. It is found that thermal treatments induce changes in its morphology, creating nanowires from particle strings. © 2005 Elsevier Ltd. All rights reserved.